Juridical Review of the Position of Substitute Notaries According to Law Number 2 of 2014 Amending Law Number 30 of 2004 on Notary Positions - Dwi Dharmayanthi, Ni Nengah; Gde Wiryawan, I Wayan (Asian Journal of Social and Humanities, 2024)
Notaries serve as custodians of legal certainty, facilitating transactions and agreements in the public sphere. However, circumstances may necessitate the appointment of substitute notaries to ensure continuity of service when a definitive notary is unavailable. This study aims to analyze the legal position and responsibilities of substitute notaries in Indonesia, as stipulated in Law No. 2 of 2014, which amended Law No. 30 of 2004 on Notary Positions. Employing normative legal research methods, this study examines the authority, obligations, and accountability of substitute notaries in drafting deeds and maintaining justice. Findings reveal that substitute notaries, despite not requiring a Master of Notary degree, possess equivalent authority and responsibility as definitive notaries during their tenure. Their duties include ensuring the validity, material truth, and confidentiality of deeds while adhering to professional ethics. This research highlights gaps in qualifications and responsibilities between substitute and definitive notaries, calling for enhanced regulation and training to maintain equitable standards. These findings have implications for legal reforms, aiming to ensure fairness, accountability, and public trust in notary services.